2021
DOI: 10.3390/plants10040810
|View full text |Cite
|
Sign up to set email alerts
|

LED and HPS Supplementary Light Differentially Affect Gas Exchange in Tomato Leaves

Abstract: Using light emitting diodes (LED) instead of conventionally used high pressure sodium (HPS) lamps as a supplemental light source in greenhouses results in a higher efficacy (µmol light per J electricity) and makes it possible to customize the light spectrum. To explore the effects of LED and HPS on gas exchange, thermal relations, photosynthesis, and water status of young tomato plants, seven genotypes were grown in a greenhouse under LED (95% red, 5% blue) or HPS lamps in four experiments differing in the fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The coatings used in this work have photoluminescence maxima at 450 and nm, which quite well correspond to the absorption maxima of tomato plants, locate the region of 440 and 675 nm [29]. Stimulating photosynthesis by increasing the pro tion of light in the blue and red regions of the spectrum has been shown in a large num of works [1][2][3][4][5][6]10,11,14]. Such stimulation can be caused both by a direct increase in amount of energy available for photosynthesis and by the adjustment of physiolo processes due to signaling pathways starting from photoreceptors.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The coatings used in this work have photoluminescence maxima at 450 and nm, which quite well correspond to the absorption maxima of tomato plants, locate the region of 440 and 675 nm [29]. Stimulating photosynthesis by increasing the pro tion of light in the blue and red regions of the spectrum has been shown in a large num of works [1][2][3][4][5][6]10,11,14]. Such stimulation can be caused both by a direct increase in amount of energy available for photosynthesis and by the adjustment of physiolo processes due to signaling pathways starting from photoreceptors.…”
Section: Discussionmentioning
confidence: 56%
“…In temperate and polar latitudes, one of the most serious problems is insufficient illumination, in particular at wavelengths used in the course of photosynthetic reactions. This problem can be solved by active backlighting using LEDs or other light sources [1][2][3][4][5][6]. However, this approach requires high economic and energy costs, which leads to an increase in carbon footprint [7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, after examining the effects of blue spectra on microgreens' growth and yield, it was found that their action was genotypic dependent [28], but this result was contradictory between experiments [29]. More generally, it was found that monochromatic blue light increased stomatal conductance [30], induced a more compact plant size [31], increased the net photosynthesis rate [32], reduced the plants' height, and increased the leaf area [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were experiments comparing HPS and LED, and no study measured the effect of SL using LED for both top-and interlighting. LED and HPS SL differentially affect photosynthetic capacity in young tomatoes [20]. Therefore, we examined the effects of different LED SL positions on cherry tomato fruit yield and quality under high irradiance.…”
Section: Introductionmentioning
confidence: 99%